Crossreactivity of an antiserum directed to the gram-negative bacterium Neisseria gonorrhoeae with the SNARE-complex protein Snap23 correlates to impaired exocytosis in SH-SY5Y cells - Almamy, Abdullah; Schwerk, Christian; Schroten, Horst (Journal of molecular neuroscience, 2017)
Early maternal infections with Neisseria gonorrhoeae (NG) correlate to an increased lifetime schizophrenia risk for the offspring, which might be due to an immune-mediated mechanism. Here, we investigated the interactions of polyclonal antisera to NG (α-NG) with a first trimester prenatal brain multiprotein array, revealing among others the SNARE-complex protein Snap23 as a target antigen for α-NG. This interaction was confirmed by Western blot analysis with a recombinant Snap23 protein, whereas the closely related Snap25 failed to interact with α-NG. Furthermore, a polyclonal antiserum to the closely related bacterium Neisseria meningitidis (α-NM) failed to interact with both proteins. Functionally, in SH-SY5Y cells, α-NG pretreatment interfered with both insulin-induced vesicle recycling, as revealed by uptake of the fluorescent endocytosis marker FM1-43, and insulin-dependent membrane translocation of the glucose transporter GluT4. Similar effects could be observed for an antiserum raised directly to Snap23, whereas a serum to Snap25 failed to do so. In conclusion, Snap23 seems to be a possible immune target for anti-gonococcal antibodies, the interactions of which seem at least in vitro to interfere with vesicle-associated exocytosis. Whether these changes contribute to the correlation between maternal gonococcal infections and psychosis in vivo remains still to be clarified.